Web information system and management of the graduate follow-up standard in a Public Institute of Higher Technological Education, Peru - Macedo-Figueroa, Julio; Antunez-Carrillo, Dennis; Diaz-Vega, Enrique; Marín-Rodriguez, William; Vasquez-Trejo, Cesar; Barrenechea-Alvarado, Julio (EAI Endorsed Transactions on Scalable Information Systems, 2023)
The objective of the research was to establish the relationship between the web information system and the follow-up standards for graduates in a Public Higher Technological Education Institution, Peru, during 2022. Materials and Methods: It corresponds to a non-experimental design of descriptive correlational design.  Results: It was shown that 67.4% of the graduates of this institution obtained a medium level in the use of the Web Information System, 19.6% acquired a higher level and 13.0% showed a minimum level, 50.0% of the graduates had a medium level, with respect to the graduate follow-up standard variable, 26.1% acquired a minimum level and 23.9% showed a high level. Conclusions There is a significant and positive relationship, obtaining a Spearman's Rho coefficient of 0.873, between the web information system and the graduate monitoring standards of the Public Higher Technological Education Institution, Peru.
Keywords: System; information; web; standards; monitoring